2021
DOI: 10.3390/nano11081932
|View full text |Cite
|
Sign up to set email alerts
|

SnS2 Nanosheets with RGO Modification as High-Performance Anode Materials for Na-Ion and K-Ion Batteries

Abstract: To date, the fabrication of advanced anode materials that can accommodate both Na+ and K+ storage is still very challenging. Herein, we developed a facile solvothermal and subsequent annealing process to synthesize SnS2/RGO composite, in which SnS2 nanosheets are bonded on RGO, and investigated their potential as anodes for Na+ and K+ storage. When used as an anode in SIBs, the as-prepared SnS2/RGO displays preeminent performance (581 mAh g−1 at 0.5 A g−1 after 80 cycles), which is a significant improvement co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It is crucial to develop efficient anode materials with high energy density, stable structure, and fast Na + diffusion channels. Although many anode materials for SIBs have been studied, such as intercalation [ 11 , 12 , 13 ], organic [ 14 , 15 , 16 ], conversion [ 17 , 18 , 19 ], alloying [ 20 , 21 , 22 ], and conversion-alloying materials [ 23 , 24 , 25 ], there is still a need to modify the existing anode materials or develop advanced anode materials with high capacity and good cycling performance, which is of great significance to realizing their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to develop efficient anode materials with high energy density, stable structure, and fast Na + diffusion channels. Although many anode materials for SIBs have been studied, such as intercalation [ 11 , 12 , 13 ], organic [ 14 , 15 , 16 ], conversion [ 17 , 18 , 19 ], alloying [ 20 , 21 , 22 ], and conversion-alloying materials [ 23 , 24 , 25 ], there is still a need to modify the existing anode materials or develop advanced anode materials with high capacity and good cycling performance, which is of great significance to realizing their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…This may increase the cost of materials and the complexity of production processes, posing a challenge for large-scale production and commercial applications. 14,15 From the perspective of improving the electrochemical performance and scalability of tin oxides, the construction of heterogeneous structures through the coupling of singleelement nanoparticles is an effective strategy to increase electrochemical reaction kinetics and enhance interfacial charge transport. 16 In this paper, heterogeneous structured nanoparticles coupled with SnO and SnO 2 are designed by a simple one-step hydrothermal method to anchor on graphene nanosheets as a LIB anode, which utilizes the reverse flow of electrons and holes at the heterogeneous interface to form space charge region, thereby achieving high reversible capacity and terrific cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In recent years, transition metal selenides (TMSes) including CoSe 2 , NiSe, FeSe 2 , and MoSe 2 have attracted significant attention as promising anode materials for KIBs owing to their low cost and high theoretical capacities. [3][4][5] Additionally, studies have shown that metal-Se bond can be easily broken compared with the metals bonded with S and O due to a larger radius of Se than those of S and O, facilitating the kinetics of the conversion reaction. 6,7 Particularly, many studies revealed that bimetallic selenides composed of two different metal components have better electrochemical properties than the countermonometallic selenides.…”
Section: Introductionmentioning
confidence: 99%
“…Potassium ion batteries (KIBs) are considered promising candidates to substitute commercial lithium ion batteries (LIBs) because of the abundance of potassium resources and their low cost, in addition to a charging‐discharging mechanism similar to that of LIBs 1,2 . In recent years, transition metal selenides (TMSes) including CoSe 2 , NiSe, FeSe 2 , and MoSe 2 have attracted significant attention as promising anode materials for KIBs owing to their low cost and high theoretical capacities 3‐5 . Additionally, studies have shown that metal–Se bond can be easily broken compared with the metals bonded with S and O due to a larger radius of Se than those of S and O, facilitating the kinetics of the conversion reaction 6,7 …”
Section: Introductionmentioning
confidence: 99%